A low friction, biphasic and boundary lubricating hydrogel for cartilage replacement. (January 2018) - Milner, Piers E.; Parkes, Maria; Puetzer, Jennifer L.; Chapman, Robert; Stevens, Molly M.; Cann, Philippa; Jeffers, Jonathan R.T.
Graphical abstract: Abstract: Partial joint repair is a surgical procedure where an artificial material is used to replace localised chondral damage. These artificial bearing surfaces must articulate against cartilage, but current materials do not replicate both the biphasic and boundary lubrication mechanisms of cartilage. A research challenge therefore exists to provide a material that mimics both boundary and biphasic lubrication mechanisms of cartilage. In this work a polymeric network of a biomimetic boundary lubricant, poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC), was incorporated into an ultra-tough double network (DN) biphasic (water phase + polymer phase) gel, to form a PMPC triple network (PMPC TN) hydrogel with boundary and biphasic lubrication capability. The presence of this third network of MPC was confirmed using ATR-FTIR. The PMPC TN hydrogel had a yield stress of 26 MPa, which is an order of magnitude higher than the peak stresses found in the native human knee. A preliminary pin on plate tribology study was performed where both the DN and PMPC TN hydrogels experienced a reduction in friction with increasing sliding speed which is consistent with biphasic lubrication. In the physiological sliding speed range, the PMPC TN hydrogel halved the friction compared to the DN hydrogel indicating the boundary lubricating PMPC network was working. A biocompatible, tough, strong and chondral lubrication imitating PMPC TN hydrogel was synthesised in this work. By complementing the biphasic and boundary lubrication mechanisms of cartilage, PMPC TN hydrogel could reduce the reported incidence of chondral damage opposite partial joint repair implants, and therefore increase the clinical efficacy of partial joint repair. Statement of Significance: This paper presents the synthesis, characterisation and preliminary tribological testing of a new biomaterial that aims to recreate the primary chondral lubrication mechanisms: boundary and biphasic lubrication. This work has demonstrated that the introduction of an established zwitterionic, biomimetic boundary lubricant can improve the frictional properties of an ultra-tough hydrogel. This new biomaterial, when used as a partial joint replacement bearing material, may help avoid damage to the opposing chondral surface—which has been reported as an issue for other non-biomimetic partial joint replacement materials. Alongside the synthesis of a novel biomaterial focused on complementing the lubrication mechanisms of cartilage, your readership will gain insights into effective mechanical and tribological testing methods and materials characterisation methods for their own biomaterials.